Effect of Deafness on Cognitive Learning: Comparative Analysis of the Opinion of Secondary School Teachers in Southern Punjab - Muhammad Nadeem Iqbal , Rabea Sani, (JIE, 2024)
Hearing impairment is a very common disability that is affecting more than 250 million children around the world. Hearing loss or deafness also put an impact on child cognitive learning as children with hearing impairment shows poor academics as compare their normal peer. The basic purpose of this study was to analyze the teacher’s opinion about the effect of deafness on cognitive learning and also measure the teacher’s opinion about nonverbal tests and their usage in school placement criteria.